Beating heart minimally invasive mitral valve surgery in patients with previous sternotomy: the operative technique and early outcomes. Issue 1 (20th January 2018) - Xu, Robert B; Rahnavardi, Mohammad; Nadal, Mart; Viana, Fabiano; Stuklis, Robert G; Worthington, Michael; Edwards, James
Abstract : Objective: Reoperative mitral valve surgery is increasingly required and can be associated with significant morbidity and mortality. The beating heart minimally invasive mitral valve surgery has a proposed benefit in avoiding the risks of repeat sternotomy, with reducing the need for adhesiolysis and cardioplegia reperfusion injury. We describe our experience with such a technique in patients with previous sternotomy. Methods: A retrospective study was performed and all patients undergoing surgery of mitral valve through a right limited thoracotomy without application of an aortic cross-clamp (beating heart) as a redo cardiac surgery between January 2006 and January 2015 were included (n=25). Perioperative data as well as the operative technique are presented. Results: Six patients (24%) had two previous sternotomies and one (4%) had three previous sternotomies. Mitral valve repair was performed in 11 patients (44%). No patient required conversion to median sternotomy. Inotropic support beyond 4 hours after operation was required in seven patients (28%). Ventilation time was less than 12 hours in 14 patients (56%) with another six patients (24%) extubated within 24 hours after surgery. Postoperative course was complicated with cerebrovascular accident in two patients (8%). In-hospital mortality was 4% (n=1). There was no 30-day mortality after discharge. Conclusions: Reoperative mitral valve surgery can be safely performed through a limited right thoracotomy approach on a beating heart while on full cardiopulmonary bypass. The technique can be associated with potentially shorter operation, shorter cardiopulmonary bypass and a less complicated recovery.